Insights on the Electrochemical Activity of Porous Carbonaceous Electrodes in Non-Aqueous Vanadium Redox Flow Batteries. Issue 14 (1st January 2017) - Mustafa, Ibrahim; Bamgbopa, Musbaudeen O.; Alraeesi, Eman; Shao-Horn, Yang; Sun, Hong; Almheiri, Saif
Abstract : Porous carbonaceous electrodes have the potential utility as electrodes for non-aqueous VRFBs due to being inexpensive, chemically stable, and electrochemically active. In this work, we provide insights on the electrochemical kinetics of [V(acac)3 ] 0 /[V(acac)3 ] + and [V(acac)3 ] 0 /[V(acac)3 ] − redox reactions at freestanding sheets of multiwalled carbon nanotubes (MWCNTs), or buckypapers (BPs), and graphitized carbon fiber-based nonwovens papers (CPs). The use of freestanding sheets eliminates the need for a metal substrate; thus, the true electrochemical response at these electrodes is measured. Even though porous carbonaceous electrodes provide high surface area for the electrochemical reaction, their porous nature poses a fundamental challenge caused by thin-film-like diffusion process; leading to a marked ohmic resistance within the pores of the electrodes. Higher current densities are obtained with the BP electrode due to their larger surface area in comparison to the CP electrode; however, the BP electrode show less efficient kinetic facility for the investigated redox couples as evident by electrochemical impedance spectroscopy and polarization curves results. Charge–discharge cycling demonstrates that porous carbonaceous electrodes may require various treatments to modify the surface chemistries to obtain improved cycling efficiencies.